Stentless pyeloplasty for paediatric uretero-pelvic junction obstruction: a 15- year experience - Mbwambo, Orgeness Jasper (Division of General Surgery, 2025)
Introduction Stenting after pyeloplasty is a traditional operative practice with the aim of ensuring a patent anastomosis and preventing complications such as urinary leakage, dehiscence and reducing risk of stricture formation. However, it has the disadvantage of complications such as infection, encrustation, migration, breakage, and increased cost of surgery to remove the stent. Therefore, recently stentless pyeloplasty has been advocated as a feasible alternative. This study aimed to evaluate the outcome of stentless dismembered pyeloplasty for congenital ureteroplevic junction obstruction. Methods We retrospectively reviewed the data of paediatric patients who underwent dismembered pyeloplasty due to congenital ureteropelvic junction obstruction (UPJO) between January 2008 and July 2022. Patients' demographics, indications for surgery, follow up data and complications were recorded on data extraction sheet. The success rate was defined as lack of need for intervention or reoperation postoperatively. This